2017
DOI: 10.3892/ol.2017.5936
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance and impact on outcomes of the gene expression levels of IGF-1, IGF-2 and IGF-1R, IGFBP-3 in patients with colorectal cancer: Overexpression of the IGFBP-3 gene is an effective predictor of outcomes in patients with colorectal cancer

Abstract: Abstract. The insulin-like growth factors (IGF) system is involved in tumor proliferation, invasion and metastasis in cancer. The current study investigated the association of IGF-1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Our analyses using the public database also indicated that an increased IGF1 mRNA was identified in patients with colon cancer as well as a shorter survival time, as compared to patients with a lower IGF1 mRNA level; HT29 colon cancer cells resistant to methotrexate expressed a significantly higher level of IGF1 mRNA as compared to their sensitive counterparts. A recent study corroborates with our view that IGF-signaling promotes the epithelial-to-mesenchymal transition (EMT) and stemness in colon cancer [ 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our analyses using the public database also indicated that an increased IGF1 mRNA was identified in patients with colon cancer as well as a shorter survival time, as compared to patients with a lower IGF1 mRNA level; HT29 colon cancer cells resistant to methotrexate expressed a significantly higher level of IGF1 mRNA as compared to their sensitive counterparts. A recent study corroborates with our view that IGF-signaling promotes the epithelial-to-mesenchymal transition (EMT) and stemness in colon cancer [ 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…CYR61 expression was associated with poor prognosis in patients with colorectal cancer [26] and it promotes cancer cells proliferation, invasion, survival, and metastasis [27, 28]. In addition to CYR61 , IGFBP3 [29] and GDF15 [30] are also effective predictors of outcomes in patients with colorectal cancer. WNT16B [31], NT5E [32], GPF15 [33], and CDC14A [34] are implicated in tumorigenesis via regulating tumor growth and EMT process.…”
Section: Discussionmentioning
confidence: 99%
“…No quantitative differences have been detected in mRNA expression of the two promoter types (class I and II transcripts), suggesting that genomic expression of IGF1 remains under a control of both P1 and P2 promoters in CRC and in normal colon. The quantitative analysis showed significantly lower expression of the total IGF1 mRNA, similarly to the results described by other authors [ 175 ]. Expression of all IGF1 transcripts in CRC was also lower compared to control samples [ 105 ].…”
Section: Igf1 Gene Alternative Splicing and Carcinogenesissupporting
confidence: 90%
“…Potential correlation between the levels of circulating IGF1 and CRC risk were reported in recent literature [ 174 ]. Similarly, lowered IGF1 protein expression was noted in cancer tissue compared with normal mucosa [ 175 ].…”
Section: Igf1 Gene Alternative Splicing and Carcinogenesismentioning
confidence: 99%